New records of the deep-sea anemone Phelliactis callicyclus Riemann-Zurneck, 1973 (Cnidaria, Actiniaria, Hormathiidae) from the Gulf of California, Mexico - Hendrickx, M.e.; Hinojosa-Corona, A.; Ayón-Parente, M. (Zootaxa, 2016)
Specimens of a deep-sea anemone were observed in photographs and video footage taken with the Remotely Operated Vehicle JASON (WHOI Deep Submergence Laboratory) in the Gulf of California, Mexico, in May 2008. Comparison of our material with photographs and description of this species available in literature indicate that the sea anemones filmed during the JASON survey are most likely to represent Phelliactis callicyclus Riemann-Zurneck, 1973. This species has previously been reported from a locality in the Gulf of California near the present record. During the JASON survey, 28 specimens of P. callicyclus were spotted in 27 locations during six dives. The specimens occurred on angular rock outcrops along the escarpments of the transform faults of the Gulf of California, between depths of 993–2543 m and at temperatures ranging from 2.3 to 4.5°C. Based on these new records, Phelliactis callicyclus appears to be widely spread in the Gulf of California.